A new single DC source five-level buck-boost inverter for single phase application - Pratomo, Leonardus Heru; Riyadi, Slamet; Tantyono, Neru Hatta (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
Recent decades have seen an amazingly fast development of inverter topology, including multilevel inverters. This kind of inverter typically functions as a buck converter; a boost converter is the reverse of this kind of inverter. The two inverters limitation to operating in either buck mode or boost mode is a negative. In this study, a five-level inverter that can operate in both buck and boost modes and only requires a single DC source input voltage is proposed. The suggested inverter will therefore have a large operational area. This new inverter's possible conduction modes are examined in order to determine the control system that will be used. A test based on computational modeling and hardware implementation is then conducted in the lab after the new control structure based on sinusoidal pulse width modulation is established. This new inverter can operate in five-level in a buck and/or boost converter in terms of the output voltage to the input voltage, according to the results of simulation and testing. The proposed new inverter outperforms traditional inverters that solely run on buck or boost.